Study and Analysis of the Drive System for a Type of Milling Machines Aiming at Performance Improvement - Mikho Mikhov; Marin Zhilevski (New Ideas Concerning Science and Technology Vol. 7, 2021)
Problems in modernization of a type of milling machines are discussed in this paper. Two additional controlled axes are applied, namely a table rotation (axis a) and tilting of this table (axis c). The machines under consideration are attributed to those with multi-coordinate drive systems. The main requirements to this system are formulated. A number of models for computer simulation with various electric drives have been developed aiming at studying their dynamic and static regimes for the respective control algorithms. The experimental research carried out confirms good performance of the electric drives applied. Detailed experimental studies confirm good efficiency of the multi-coordinate driving system applied. The results of this study can be used in the design and set up of such multi-coordinate drive systems.